HÁ UMA LEI NO MEIO DO CAMINHO: LUTA PARA PERMANECER NA TERRA DOS FUNDOS E FECHOS DE PASTO NA BAHIA. - MOREIRA DE ALCÂNTARA, DENILSON; GERMANI, GUIOMAR INEZ; FURTADO SAMPAIO, JOSE LEVI (Terra Livre, 2015)
nt